THE EFFECT OF PRICE, PROMOTION, AND E-SERVICE QUALITY ON PURCHASE DECISIONS ON TOKOPEDIA E-COMMERCE IN BOGOR CITY - Ramadhan, Fadlan; Samsuri, Samsuri; Gunawan, Rachmat (Universitas Nusa Cendana, 2025)
The present research examines the impact of pricing, promotional strategies, and quality of electronic services on consumer buying choices on Tokopedia e-commerce. Using a quantitative approach with random sampling, as many as 100 samples as respondents. Data were analyzed through multiple linear regression using SPSS 25. The results showed that pricing, promotional strategies, and quality of electronic services had a notable and meaningful impact simultaneously on consumer buying choices, and the most dominant variable was the pricing variable. Partially, the pricing variable had a notable and meaningful impact on consumer buying choices, promotional strategies had a notable and meaningful impact on consumer buying choices, and quality of electronic services had a notable and meaningful impact on consumer buying choices. Keywords: Price; Promotion; E-Service Quality; Purchasing Decisions